Constructing White-Collar Crime : Rationalities, Communication, Power - Savelsberg, Joachim J. (Law in Social Context, 2016)
Based on Joachim J. Savelsberg and Peter Brühl, Politik und Wirtschaftsstrafrecht: Rationalitäten, Kommunikationen und Macht (Opladen: Leske & Budrich, 1988), revised, translated, and with a new chapter on the United States.